KORELASI ANTARA MENTAL TOUGHNESS DENGAN ACHIEVEMENT GOALS DAN MOTIVASI OLAHRAGA PADA PEMAIN VOLI UKM UPI - Nun Alinsa, - (2020)
This aim of research was to test the relationship mental toughness with the achievement goals and to know the relationship between mental toughness with sport motivation to volleyball players at UPI, the method used is correlates with the design of a double paradigm simple correlation research. The samples in this study were volleyball players who joined in the UPI volleyball UKM with a sample number of 90 people. Sampling techniques use a total sampling. The instruments used are adaptations of the Mental Toughness Questionnaire-48 questionnaire, Achievement Goals Questionnaire Sport-12, and Sport Motivation Scale-6. Data analysis uses correlation Rank Spearman to test the relationship between mental toughness and achievement goals and to test the relationship between mental toughness and exercise motivation. The conclusion of this research is there is a significant relationship between mental toughness and achievement goals. That means the higher the mental toughness, the higher the achievement goals, with contribution mental toughness to the achievement goals of 9.4%. And there is a significant relationship between mental toughness and sport motivation. That means the higher the mental toughness, the higher the motivation of exercise, with contribution mental toughness to the sport motivation of 15.1%. Recommendations from this research are further improved research samples, to determine the level and test the relationship between mental toughnes, achievement goals and sport motivation to elite athletes and other more specific categories of athletes. Keywords: Mental Toughness, Achievement Goals, Sport Motivation, Volleyball Player